(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Ground water is the main and most important source of water supply in Bangladesh. But the water has been contaminated by arsenic and has become a public health hazards in our country. About 35-70 million people in 61 out of 64 districts of Bangladesh are consuming arsenic contaminated water and are prone to develop health hazards due to chronic arsenicosis. Chronic exposure to arsenic may cause wide range of carcinogenic & non-carcinogenic health effects. So far there is no specific management for chronic arsenic toxicity, though the magnitude of the disease is potentially toxic & fatal. If effective treatments are not provided to those sufferers, it will bring a negative impact in our country as far as economical growth is concerned. Government and its existing resources alone will not be able to meet the challenges due to arsenic toxicity. The challenges are as under: a) creation of mass awareness about the danger of drinking arsenic contaminated water and to provide arsenic free, bacteriologically and chemically safe alternative source of drinking water to the vast number of the population of the country at risk of developing arsenicosis, b) diagnosing all arsenicosis patients and provide effective management of their condition. The probable & suitable solutions of chronic arsenic toxicity have been explored. Recommended steps include rain water harvesting, treatment of surface water, proven safe and sustainable technologies implemented under and piped water supply. Besides for further improvement of diagnosis and management of chronic arsenicosis, following steps are needed- establishing and updating an arsenicosis patients data base for early identification of the arse-nicosis patients and establishing an easy and effective referral system so that arsenicosis patients are screened at rural level can be transferred to appropriate centre. Since existing resources of our country cannot fight against these environmental hazards, without the involvement of private sectors and international donor agencies all efforts will be un-sustainable. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014